Peripartum HIV infection in very low birth weight infants fed ‘raw’ mother’s own milk - Melantha Coetzee (Southern African Journal of HIV Medicine, 2019)
Background: HIV-exposed very low birth weight (VLBW) infants (≤ 1500 g) are considered at high risk of peripartum mother-to-child HIV transmission (MTCT). In the past, they received formula to prevent breast milk related HIV transmission. This denied them the benefits of breast milk, thus exposing the infant to the risk of necrotising enterocolitis (NEC). From 2010, ‘raw’ mother’s own milk (rMOM) has been recommended for term infants whose mothers’ received antenatal antiretroviral therapy (ART). At the same time, the infant received antiretroviral (ARV) prophylaxis as per the National Prevention of MTCT programme.